Bond–slip behavior of fiber-reinforced polymer/concrete interface in single shear pull-out and beam tests. (March 2016) - Mohammadi, Tayyebeh; Wan, Baolin; Harries, Kent A
It has been assumed that the fiber-reinforced polymer/concrete interface is subjected to in-plane shear condition when intermediate crack debonding failure occurs. Therefore, the single shear pull-out test results are often used to predict the intermediate crack debonding failure in beams. In this study, the behavior of fiber-reinforced polymer-strengthened concrete beams and single shear pull-out specimens were studied experimentally and numerically. The bond–slip behavior of the fiber-reinforced polymer/concrete interface was obtained by single shear pull-out and beam tests. In all beam specimens, a concrete wedge located at the edge of the notch detached with the fiber-reinforced polymer debonding failure. This phenomenon shows that the initiation of debonding is due to a diagonal crack formation close to the major flexural/shear crack inside the concrete. The diagonal crack formation is due to a local moment at the tip of the notch. This causes the different stress state and slip of the fiber-reinforced polymer/concrete interface of beam specimens from that of the pull-out specimens. It is found that the bond–slip relation obtained from the pull-out test does not represent the bond–slip relation of the fiber-reinforced polymer/concrete interface in the fiber-reinforced polymer-strengthened concrete beams, and it cannot be directly used for predicting the load capacity of the fiber-reinforced polymer-strengthened concrete beams.